Needs Analysis of Students in Dialectology Learning at Toraja Christian University of Indonesia - Resnita Dewi; Daud Rodi Palimbong; Theresyam Kabanga; Roni La’biran (AL-ISHLAH: Jurnal Pendidikan, 2024)
This research aims to analyze the needs of students at the Toraja Christian University of Indonesia in dialectology learning. The study is beneficial in providing profound insights into the needs and preferences of students in dialectology learning, assisting the university in developing a more relevant and effective dialectology course. Furthermore, by understanding the student's needs, the university can allocate learning resources more efficiently, including providing more suitable teaching materials, effective teaching methods, and improving learning facilities. This research is a mixed-methods study, combining both quantitative and qualitative analyses. Data for this study were obtained from 46 students in the Indonesian Language and Literature Education Program at Toraja Christian University of Indonesia who enrolled in the Dialectology course during the academic year 2022/2023. Data were collected through survey and interview techniques. The results of the research indicate that students' needs in dialectology learning include understanding the learning materials, effective teaching methods, required learning resources, and desired practical experiences. Students' expectations and motivations in dialectology learning vary, ranging from deepening their understanding of language and culture and learning about dialectal differences in their society to contributing to language preservation.